2000
DOI: 10.1007/bf02818714
|View full text |Cite
|
Sign up to set email alerts
|

Effects of subinhibitory concentrations of nitroxoline on the surface properties ofEscherichia coli

Abstract: Nitroxoline (5-nitro-8-quinolinol; NIQ) at subinhibitory concentrations (sub-MIC) decreased the adherence of uropathogenic Escherichia coli to catheter surface and significantly enhanced cell surface hydrophobicity. The surface hydrophobicity increased in the presence of sub-MIC of NIQ and also in an excess of Mg2+. The effect of NIQ on the cell surface was not related to the bacteriostatic effect of this agent. The increase in nitrogen and decrease in phosphate content in the cell surface was found in the pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 27 publications
1
14
0
Order By: Relevance
“…The values we obtained for C-(O, N)/C (0.337 and 0.314 for free and bound EPS respectively, Table 3) are higher than those reported for proteins (0.26-0.293) but lower than those reported for polysaccharides (0.833). [47][48][49][50] Similarly, (CdO)/C + (O-C-O)/C values for free and bound EPS (0.144 and 0.141, respectively) are close to those reported for polysaccharides (0.167) and lower than those for proteins (0.225-0.279). Atomic ratios N/C, O/C, and P/C are higher for bound EPS, whereas N/P is higher in free EPS (Table 3).…”
Section: Resultssupporting
confidence: 80%
“…The values we obtained for C-(O, N)/C (0.337 and 0.314 for free and bound EPS respectively, Table 3) are higher than those reported for proteins (0.26-0.293) but lower than those reported for polysaccharides (0.833). [47][48][49][50] Similarly, (CdO)/C + (O-C-O)/C values for free and bound EPS (0.144 and 0.141, respectively) are close to those reported for polysaccharides (0.167) and lower than those for proteins (0.225-0.279). Atomic ratios N/C, O/C, and P/C are higher for bound EPS, whereas N/P is higher in free EPS (Table 3).…”
Section: Resultssupporting
confidence: 80%
“…These effects are not limited to E. coli strains, but also occur with many different bacteria [1][2][3][4][5][6]. Several researchers have reported that sub-MICs of some antibiotics increase the surface hydrophobicity and the ability of bacteria to adhere to epithelial cells [13,14].…”
Section: Discussionmentioning
confidence: 99%
“…Many authors have described the effects of these environmental parameters on hydrophobicity and charge (Beck et al 1988;Herben et al 1990;Van Der Mei et al 1993;Latrache et al 1994;Briandet et al 1999;Latrache et al 2000). Literature data (Rouxhet and Mozes 1990) reported that the hydrophobicity and charge were insufficient to explain the adhesion phenomenon.…”
Section: Introductionmentioning
confidence: 94%